Omnidirectional iridescence via cylindrically-polarized femtosecond laser processing - Livakas Nikolaos (Institue of Optics and Electronics, Chinese Academy of Sciences, 2020)
We report the femtosecond (fs) laser fabrication of biomimetic omnidirectional iridescent metallic surfaces exhibiting efficient diffraction for practically any angle of light incidence. Such diffractive behavior is realized by means of multi-directional low-spatial-frequency, laser-induced periodic surface structures (LSFL) formed upon exploiting the cylindrical symmetry of a cylindrical vector (CV) fs field. We particularly demonstrate that the multi-directional gratings formed on stainless steel surface by a radially polarized fs beam, could mimic the omnidirectional structural coloration properties found in some natural species. Accordingly, the fabricated grating structures can spatially disperse the incident light into individual wavelength with high efficiency, exhibiting structural iridescence at all viewing angles. Analytical calculations using the grating equation reproduced the characteristic variation of the vivid colors observed as a function of incident angle. We envisage that our results will significantly contribute to the development of new photonic and light sensing devices.